Consumer preferences before and after a food safety scare: An experimental analysis of the 2010 egg recall. (January 2017) - Li, Tongzhe; Bernard, John C.; Johnston, Zachary A.; Messer, Kent D.; Kaiser, Harry M.
Highlights: Economic experiments investigated consumers' willingness to pay (WTP) for eggs. One experiment was conducted just before and the other soon after a major egg recall. The average WTPs were not significantly different before and after the recall. WTP for organic eggs significantly increased in the negative information treatment. Balanced information had a positive effect on consumer WTP for conventional eggs. Abstract: In August 2010, more than half a billion eggs were recalled in the U.S. because of a Salmonella outbreak. This study examines the effect of the recall with a unique pair of auction experiments investigating willingness to pay (WTP) for conventional and organic eggs, one conducted shortly before and one right after the recall with the same participants. In addition to the before and after bids, participants bid again after a negative information or balanced information treatment about the event. Accompanying surveys showed consumers had a high level of awareness of the recall but less knowledge of specific details, and viewed information on egg farm conditions as very important in their WTP. While there were no significant before and after differences, WTP for organic eggs significantly increased in the negative information treatment, and balanced information had a positive effect on consumer WTP for conventional eggs.